Contribution of Apoptosis to Rheumatosis Arthritis Pathogenesis. Probable Ways for the Process Control - Goltsev, A. N.; Ostankova, L. V.; Rassokha, I. V. (Problems of Cryobiology and Cryomedicine, 2002)
The problem of search for the adequate treatment ways of rheumatoid arthritis (RA) is considered. Obviously, realisation of the optimisation ways for this pathology treatment is impossible without the decoding of fundamental mechanisms for the RA initiation and maintenance. The possibility to use the products of embryo fetoplacental complex (PEFPC) as the modulators of immune reactivity state during RA, and particularly, to control the apoptosis processes is proposed.